(untitled) - Jans, James P. (New York, 1964)
This concise text is geared toward students of mathematics who have completed a basic college course in algebra. Combining material on ring structure and homological algebra, the treatment offers advanced undergraduate and graduate students practice in the techniques of both areas.
Keywords: Rings (Algebra),Vành (Đại số)